2021
DOI: 10.1101/2021.12.23.473944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-nucleus RNA Sequencing and Spatial Transcriptomics Reveal the Immunological Microenvironment of Cervical Squamous Cell Carcinoma

Abstract: To understand the etiological, structural, and immunological characteristics of cervical squamous cell carcinoma (CSCC), we conducted single nucleus RNA sequencing (snRNA-seq) and spatial transcriptomics (ST) experiments for cervical samples from 20 individuals. When exploring the possible factors shaping the intra-individual immune heterogeneity in CSCC, we identified a cluster of cancer-associated fibroblasts (CAFs) enriched around some tumors, which highly expressed ACTA2, POSTN, ITGB4, and FAP. Results sho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
(178 reference statements)
0
6
0
Order By: Relevance
“…A third study on human cervical squamous cell carcinoma also identified a diverse population of immune cells 17 . Although they identify immune cells, these studies might underestimate the true fraction of immune cells present in their natural conditions after all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third study on human cervical squamous cell carcinoma also identified a diverse population of immune cells 17 . Although they identify immune cells, these studies might underestimate the true fraction of immune cells present in their natural conditions after all.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, Gouin et al performed snRNA-seq on fresh frozen bladder tumor samples and identified a fraction of immune cells (5%) comprising T-cells, dendritic cells, macrophages, and B-cells defined by classic immune marker genes 4 . A third study on human cervical squamous cell carcinoma also performing snRNA-seq identified a diverse population of immune cells as well 18 . Although they identify immune cells, these studies might underestimate the true fraction of immune cells present in their natural conditions after all.…”
Section: Discussionmentioning
confidence: 99%
“…Ou et al. found unique immune cell types enriched in tumour areas with different metabolic activity 9 . By analyzing neighboring cell composition from spatial transcriptomics data, Cong et al.…”
Section: Figurementioning
confidence: 99%
“…8 Ou et al found unique immune cell types enriched in tumour areas with different metabolic activity. 9 By analyzing neighboring cell composition from spatial transcriptomics data, Cong et al identified a specific macrophage subgroup for SARS-CoV-2 clearance and inflammation resolution 10 (Figure 1).…”
mentioning
confidence: 99%
“…Consequently, the TME has the potential to switch the immune system from an anti-tumor mode to a pro-tumor state, depending on its composition ( Figure 1 ). Encouragingly, therapeutic approaches targeting TME components, including myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs), and regulatory T cells (Tregs), and have demonstrated promising anti-tumor activity in both preclinical and clinical studies ( 12 18 ). Therefore, exploring the predictive and therapeutic values of the TME holds significant promise for advancing gynecologic cancer treatment.…”
mentioning
confidence: 99%